Microbial Genome Databases: A User’s Perspective - JERRINE JOSEPH; SAMEER HASSAN; VASANTHI RAJENDRAN; VANAJA KUMAR (International Journal of Pharma and Bio Sciences, 2010)
The challenge of assimilation of the accumulating wealth of information necessitates the urge for having a comprehensive database. Such database can be used as an important tool in assisting scientists to decipher a host of biological phenomena ranging from the structure of biomolecules and their interaction to the whole metabolism of organisms and the evolution of species. This knowledge helps facilitate the fight against diseases and assists in the development of medications. The efforts of data integration through data warehouse or data federation are needed to answer the complex analytical queries in the bioscience. The aim of this paper is to deal with the data integration of various databases.